Total extrusion of a silicone encircling band through the muscle insertions presenting as orbital cellulitis. (August 2014) - Kotoulas, Andreas; Symeonidis, Chrysanthos; Kalantzis, George; Droutsas, Konstantinos; Koutsandrea, Chryssanthi; Georgalas, Ilias
Abstract Introduction: We present an unusual case of anterior migration of a solid silicone encircling band 9 years after scleral buckling surgery. Materials and Methods: An 83-year old woman presented with acute onset of pain and discharge in her left eye. She had undergone cataract surgery complicated by endophthalmitis and managed with pars plana vitrectomy nine years earlier. Results: The patient was treated with transection and removal of the extruding encircling band. Pain ceased within two days. Two weeks postoperatively, the conjunctiva was well adapted without any discharge, ocular motility was as preoperatively. Discussion: Anterior migration of an encircling band through all four rectus muscle insertions is a very uncommon late complication following scleral buckling surgery. The remarkably good preservation of ocular motility in our case can be attributed to the slow advancement of the encircling band over nine years, which allowed a gradual reattachment of the rectus muscle insertions to the sclera.